Hotel nómada - Nooteboom, Cees, 1933- (Ojo del tiempo, 2014)
In a collection of essays and travelogues, the author of Roads to Santiago recounts his journeys around the world, sharing his keen observations and reflections on people and places both conventional and exotic.